Analysis of Teacher Constraints in the Distance Learning System in Biology Learning at Senior High School of Brebes Regency During the COVID-19 Pandemic - Ipah Budi Minarti; Lissa Lissa (International Journal of Research in Education, 2022)
The change in learning which was originally face-to-face turned into distance learning suddenly and simultaneously this certainly caused various obstacles for teachers in the learning process. This study aims to identify the teacher's obstacles in the Distance Learning System in Biology learning at Senior High School  of Brebes Regency during the COVID-19 pandemic. The study used descriptive qualitative methods by distributing online questionnaires to the teachers. The population in this study were Biology teachers at Senior High School in Brebes Regency, totaling 36 teachers. Sampling used a total sampling consisting of 36 teachers. The instrument used is a teacher's questionnaire in planning, implementing learning, design, and learning media, learning technology/application, and assessment/evaluation. The instrument in the form of a teacher questionnaire used has been validated by researchers with expert validation. The results of the study indicate that the most dominant constraint is the constraint in the very high category, namely the planning constraint of Distance Learning System (68%) Followed by the implementation constraint with a percentage (62%) in the high category then the assessment and evaluation constraint with a percentage (61%). Meanwhile, other constraints are design and media constraints by 60% in the high category and technology/application constraints by 60% in the high category. Referring to these results, teachers in the Distance Learning System still find problems in planning, implementation, media and methods, technology/application, and evaluation/assessment. One of these obstacles must be overcome, one of which is to overcome obstacles in technology/application, namely by replacing the easier-to-use learning media, namely GoogleMeet, or Zoom Meeting, where both applications include official applications supported by the Ministry of Education and Culture in subsidizing internet quotas.